Semantic-based automated reassembly of heritage fragments - Marie-Morgane Paumard (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Artificial intelligence provides archeologists and conservators with solutions to many problems. Among them, artifact reconstruction would surely benefit from smart automation. After the spread of the vision-based reassembly techniques, that use either fractures or pattern continuity, the last decade has seen the rise of semantic-based algorithms that allow performing computer vision tasks using the meaning of what is represented. We expect that such methods would help to solve some of the most difficult heritage problems that cannot be addressed by traditional methods, often because the fragments are too eroded to make continuity-based deductions.